The Effect of School Climate And Family Social Support on Subjective Well-Being of Middle School Students In Modern Islamic Boarding School - Husaini, Rizkia; Dadeh, Tarmidi; Hasnida, Hasnida (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The transition from elementary to middle school for teenage students in Islamic boarding schools is uniquely challenging. They must be independent since they are apart from their family. There are a lot of chances and pressures, and if students can't handle them, it can cause high stress, demotivation, and poor mental health, which impacts their subjective well-being. This research examined the effect of school climate and family social support on the subjective well-being of 320 middle school students in modern Islamic boarding schools. Convenience sampling was used as a sampling method, and a Likert scale was used to collect data. CFA was used to examine the validity construct. Multiple regression analysis was utilized to analyze data with SPSS 24 program. The findings of the study were that (1) school climate has a positive effect on subjective well-being and (2) family social support has a positive effect on subjective well-being. (3) School climate and family social support both have a positive effect on subjective well-being. This study shows that establishing a positive school climate and strong family social support may improve students' subjective well-being.